Peningkatan keterampilan representasi penyajian data melalui model pembelajaran kooperatif tipe numbered head together (nht) pada peserta didik Kelas IV sekolah dasar - Regita Cahyani; Siti Kamsiyati; Idam Ragil Widianto Atmojo (Universitas Sebelas Maret, 2021)
Abstract. This research aims to improve representation skills of data presentation for fourth grade students of Mangkuyudan Elementary School Surakarta in 2018/2019 academic year by by applying Number Head Together (NHT). This Classroom Action Research consisted of two cyles with two learning in each cycle. Subject in this research were students and teacher in IV grade of Mangkuyudan Elementary School Surakarta. Research data collection by way of interviews, observations, test, and document analysis. Source triangulation and technical triangulation used for data validity. The data in this research used descriptive comparative analysis techniques and interactive analysis model by Miles and Huberman. Classical completeness of students in initial condition was 3,33%, in first cycle showed 40%. then in second cycle showed 80%.